Serie van 5 tekeningen gemaakt voor "E. Mandel, Inleiding in de marxistiese economie" (65/312) - Willemen, Kees, (1970)
Serie van 5 tekeningen gemaakt voor "E. Mandel, Inleiding in de marxistiese economie" (65/312).